From Campus To Career: Understanding And Addressing Placement Anxiety Among Undergraduate Students (International Journal of Environmental Sciences, 2025)
One of a person's most significant life events is making the transition from college to a professional career. The “campus-to-career” transition represents a critical phase marked by both anticipation and uncertainty. In addition to being a time of personal and academic growth for many undergraduate students, the campus experience is also a time when expectations regarding future employment begin to solidify. The pressure to get a job before graduation grows stronger as students progress through their education, especially in their final years. While this stage should ideally be characterized by excitement and hope for the future, it is frequently overshadowed by a growing sense of stress, self-doubt, and anxiety collectively as placement anxiety.Placement anxiety as emotional stress and psychological unease experienced by students as they prepare to enter the job market. It is a multifaceted phenomenon influenced by societal expectations, personal aspirations, peer competition, academic performance, economic uncertainty, and other factors. For undergraduate students in particular, who may be stepping into the job market for the first time, the stakes feel exceptionally high. The fear of not securing employment, the uncertainty surrounding career choices, and the pressure to meet familial and societal expectations can significantly impact a student’s mental well-being. Anxiety can even result in more serious consequences, such as chronic stress, burnout, or mental health conditions like depression, in some instances. The modern employment landscape further compounds these challenges. In today's rapidly evolving job market, where automation, globalization, and shifting industry demands constantly redefine the skills required, students are compelled to not only perform academically but also to cultivate a portfolio of diverse competencies. Recruiters increasingly seek candidates who demonstrate technical skills, problem-solving abilities, leadership potential, and adaptability expectations that may not always be fully met within the traditional academic framework. As a result, many students feel unprepared or under qualified, leading to heightened anxiety during placement season.